Development and Initial Validation of a Life Event Scale for Students - Linden, Wolfgang (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study represents a readaptation of the Social Readjustment Rating Scale for college and university students. Student-typical items were empirically derived and normative data on each item were collected from a sample of 176 students. An initial attempt to validate this new scale indicated significantly higher frequencies of medical illness, seeking of psychological help, and academic failures in individuals with above average life change.